Can you explain why does the following Jacobian chain rule holds true?

$$ \\ \it J_{f \circ R}(x) = J_{f}(Rx) \circ R $$

Where, $ \ f\in C^2(\Omega; \mathbb{R} ),\ \Omega\subset\mathbb{R^2},\ and \ \it R \in SO(2) $ denotes a $2\times2$ matrix with det($\it R$) = 1 and it can be written as $\begin{pmatrix} \cos \alpha & -\sin \alpha \\ \cos \alpha & \sin \alpha \end{pmatrix}$

In general Jacobian chain rule is,

$$ \\ \it J_{f \circ g}(x) = J_{f}(g(x)) \circ J_{g}(x) $$

so by that logic, it should be,

$$ \\ \it J_{f \circ R}(x) = J_{f}(Rx) \circ J_{R}(x) $$ but obviously $ J_{R}(x) $ it does not make any sense to me. Can you please explain?


Let $A$ be any matrix in $\mathbb{R}^{2\times 2}$ and consider the mapping $g : \mathbb{R}^2\to\mathbb{R}^2$ defined by $g(x) = Ax$. Then according to the chain rule

$$ J_{f\circ g}(x) = J_f(g(x))\circ J_g(x) $$

Given our definition of $g$ it follows that

$$ J_g(x) \equiv A $$

and hence

$$ J_{f\circ g}(x) = J_f(Ax)\circ A $$


Your problem really boils down to the following question: what is the Jacobian of a linear map?

Let $\ell\colon\mathbb{R}^n\rightarrow\mathbb{R}^n$ be a linear map, then for all $x,h\in\mathbb{R}^n$, one has: $$\ell(x+h)=\ell(x)+\ell(h)=\ell(x)+\ell(h)+o(h),$$ so that $\mathrm{d}\ell_x\colon h\mapsto\ell(h)$, it other words: $\mathrm{d}\ell\equiv\ell$ and $J_x\ell=\ell$ for any $x\in\mathbb{R}^n$.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.